A SURVEY OF KNOWLEDGE AND ATTITUDE OF THE GENERAL PUBLIC TOWARDS EPILEPSY IN LAHORE, PAKISTAN - Naeem, Farooq; Ayub, Muhammad; Kingdon, David; Mujtaba, Muhammad; Zaidi, Qaiser Abbas; Bhatti, Faiz; Chaudhari, Haroon Rashid (Journal of Pakistan Psychiatric Society, 2007)
Objective: To explore the ideas people have towards epilepsy.Design: The qualitative methods were used in the first step while in second stage a cross sectional design was used.Place and duration of study: The study was conducted at the Ganga Ram Hospital medical outpatients in Lahore, Pakistan from November 2003 to April 2004.Subject and Methods: A focus group was conducted to explore the beliefs people have towards epilepsy. Seven patients and their carers who were attending medical outpatients participated in this group discussion. On the basis of this a survey form was formulated. This form was used to gather information from a larger sample in the next step in which all those attending this service during the study period were contacted. Those who consented were asked questions from the survey.Results: Nearly 90% respondents were aware of epilepsy. Ninety three percent respondents believed that epilepsy is treatable. Nearly 95% people believed that if epileptic patients are treated, they recover completely. However, there were variations in people’s beliefs about causes of epilepsy as well as how and who should treat it.Conclusion: Nearly half of our sample derived from a big urban centre believed in unscientific causes of epilepsy. There is urgent need to educate general public on this important issue.Key words: Knowledge, Attitude, Epilepsy, Pakistan.